Exigência nutricional de cálcio e de fósforo de codornas de corte (Coturnix cotunix sp) em crescimento - Silva, Ronaldo Martins da (2008)
Two experiments were carried out at the Experimental Farm of Maringá University, to estimate the calcium and phosphorus requirements for the maximum performance of meat quail in growing, (1 to 14 days of age) and (15 to 35 days of age). In the first experiment, one thousand two hundred and fifty meat quail were allocated in a factorial scheme 5x5 (calcium levels = 0.65; 0.76; 0.87; 0.98 and 1.09 % x phosphorus levels = 0.12; 0.22; 0.32; 0.42 and 0.52 %), totalizing twenty five treatments, with two replications of Twenty-five quails per experimental unit. Differences had not been observed (P>0.05) between levels of available calcium and phosphorus. The different calcium levels did not affect (P>0.05) birds performance. Body weight, weight gain and optic density were influenced in a quadratic form (P<0.05) by phosphorus levels and phosphorus requirement was estimate in 0.41%. It was concluded that the levels of 0.65% calcium and 0.41% phosphorus in diet was enough to attend the requirement of meat quail in initial growing phase (1 to 14 days of age). the second experiment, for performance one thousand five hundred meat quails were allocated in a factorial scheme 5x5 (calcium levels = 0.61; 0.71; 0.81; 0.91 and 1.01 % x phosphorus levels = 0.29; 0.34; 0.39; 0.44 and 0.49 %), totalizing twenty five treatments, with two replications of thirty quails per experimental unit. Differences had not been observed (P>0.05) of the levels of calcium and phosphorus on birds performance. Optic density were influenced in a quadratic form (P<0.05) by phosphorus levels and phosphorus requirement was estimate in 0.41%. In calcium and phosphorus balance were used ninety meat quails allocated in a factorial scheme 3x3 (calcium levels = 0.61; 0.81 and 1.01 % x phosphorus levels = 0.29; 0.39; and 0.49 %) totalizing nine treatments, with two replications of five quails per experimental unit. It was observed a linear effect (P<0.05) in the intake and excretion of calcium with the increase in the calcium levels in diets. It was concluded that the levels of 0.61% calcium and 0.41% phosphorus in diet were enough to attend the requirement of meat quail in growing (15 to 35 days of age).